TiC with shell-like bionic structure x Reinforced copper-based composite material and preparation method thereof

Through hot-pressing sintering and in-situ reaction diffusion processing, TiCx reinforced copper-based composite materials with shell-like bionic structures are prepared, which solves the mutual constraints between strength, hardness and conductivity of existing materials and achieves high strength, high hardness, Improvement of comprehensive properties such as good conductivity and toughness.

CN116516210BActive Publication Date: 2025-01-24NORTHEASTERN UNIV CHINA +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310469190.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2025-01-24
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

While improving strength, hardness and conductivity, existing copper-based composite materials are difficult to synergistically improve toughness and wear resistance, and the preparation process is complex and it is difficult to achieve industrial production.

Method used

The Ti3ALC2 block material with a shell -like bionic structure is prepared by the thermal pressure sintering system, and the copper is performed in situ at high temperature at high temperature to form a high -oriented non -chemical measurement number TICX as the ceramic phase, which is evenly distributed in the copper base to achieve realizing it to achieve the realization Composite material of the "brick-mud" structure.

Benefits of technology

The high -strength, high hardness, good conductivity and thermal conductivity of copper -based composite materials are realized, while improving the toughness and abrasion resistance of the material, and the process is simple and reliable, suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116516210B_ABST
    Figure CN116516210B_ABST
Patent Text Reader

Abstract

TiC of shell-like bionic structure of the present invention x The invention relates to a reinforced copper-based composite material and a preparation method thereof, belonging to the technical field of copper-based electrical contact materials. The copper-based composite material is a ceramic phase TiC x and matrix copper, TiC x The volume fraction of Ti is 45-65%, and the balance is copper. The preparation method is: hot pressing and sintering the micro-nano flake Ti 3 AlC 2 Densification, obtain Ti with shell-like bionic structure 3 AlC 2 The block is then subjected to in-situ reaction diffusion with copper under protective gas or vacuum conditions at high temperature to produce flake TiC in-situ. x The reinforced copper-based composite material has a shell-like "brick-mud" structure at the microscopic level. This structure has a high strengthening and toughening mechanism, which is beneficial to improving the mechanical properties of the material and maintaining good connectivity of the copper matrix, which is beneficial to electron transmission and improves electrical conductivity. This material is expected to be used in electrical switches, circuit breakers, contactors, etc., which is of great significance for ensuring the safe and efficient transmission of current and promoting energy conservation and consumption reduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of copper-based electrical contact materials, and particularly relates to TiC with shell-like biomimetic structure. x Reinforced copper-based composite material and preparation method. Background Art

[0002] Material strengthening and toughening, as well as structural-functional integration, are not only at the forefront of international science but also crucial demands in key sectors such as the national economy. However, different material properties, such as strength, toughness, and electrical conductivity, often constrain each other. Furthermore, as complex service environments place increasingly stringent demands on material performance, traditional material preparation methods offer increasingly limited scope for designing and manipulating composition and microstructure. Therefore, the exploration of new approaches is urgently needed. Shell-like structures are considered a source of inspiration for designing high-strength, high-toughness materials. These outstanding mechanical properties are primarily attributed to the interaction between stone flakes and the organic matrix within the typical "brick-and-mortar" structure. Therefore, developing copper-based composites with shell-like structures that possess not only high mechanical properties such as strength, toughness, and hardness, but also excellent electrical and thermal conductivity is of great significance for the application of copper-based electrical contact materials.

[0003] Ti3AlC2 is a ternary nano-layered metal-ceramic composite material with covalent bonds, ionic bonds and metallic bonds. Therefore, it has the characteristics of both metals and ceramics, such as the high melting point, high modulus, high temperature resistance, low density of ceramics and the electrical conductivity and machinability of metals. In addition, compared with other ceramic-ceramic phase materials (such as Al2O3, SiC, etc.), Ti3AlC2 can undergo wettability in situ reaction with copper, making it an ideal ceramic phase for copper-based composite materials. Therefore, the micro-nano flaky Ti3AlC2 powder is subjected to hot pressing and sintering to realize a Ti3AlC2 bulk material with a shell-like bionic structure, and then the Ti3AlC2 bulk material and metallic copper are placed in a high-temperature furnace with a protective gas for in-situ diffusion treatment, and finally a flaky TiC with a shell-like bionic structure is obtained. x Reinforced copper matrix composites.

[0004] At present, regarding ceramic-reinforced copper-based composite materials with bionic shell-like structures and their preparation methods, Patent 1 (CN109524251A) discloses a preparation method and application of titanium-modified Ti3AlC2-reinforced copper-based electrical contacts; Patent 2 (CN113512658A) discloses a Ni-doped Ti3AlC2 / Cu composite material for inhibiting the decomposition of Ti3AlC2 and its preparation method; Patent 3 (CN112935250A) discloses a functional gradient material of Cu and Ti3AlC2 for pantograph slides and its preparation method; Patent 4 (CN114427049A) discloses a Cu-TiCx composite material and its preparation method.

[0005] The above patents 1-3 all adopt powder metallurgy technology, among which patents 1 and 2 are methods of modifying or doping Ti3AlC2 with metal elements to inhibit the decomposition of Ti3AlC2 and prevent Al atoms from diffusing and dissolving in the matrix copper. The ceramic phase Ti3AlC2 is distributed in the copper matrix in a discontinuous manner and the introduced metal elements can react in situ to form compounds at the interface between the two phases, which is not conducive to the improvement of mechanical properties; patent 3 adopts the method of powder stacking to prepare a composite material with a gradient structure. The preparation of mixed powder, powder stacking and other process operations are complicated and it is difficult to prepare large samples, which is not conducive to industrial production; patent 4 is a Ti3AlC2 / Ti3SiC2 porous skeleton that is continuous in three-dimensional space, and then infiltrates metal copper at high temperature to obtain an in-situ reaction to generate TiC x Enhanced copper-based composite ceramic phase. However, the performance of the material is closely related to the microstructure. Although the strength and hardness of the copper-based composite material described in Patent 4 are improved, the electrical conductivity is reduced too much. This is because Patent 4 lacks a specific spatial structure design (such as orientation design). Increasing the ceramic phase content alone will lead to a decrease in the electrical and thermal conductivity of the material, while increasing the matrix phase content will limit its strength and hardness. This makes the material strength, hardness, wear resistance and electrical conductivity mutually restricted, making it difficult to improve them synergistically. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the present invention provides a TiC shell-like bionic structure. xThe invention relates to a reinforced copper-based composite material and a preparation method thereof, with the aim of preparing a copper-based electrical contact material with high strength and hardness, good thermal properties and electrical conductivity by a simple and reliable process. A Ti3AlC2 precursor material with a shell-like bionic structure is prepared by hot-pressing and sintering Ti3AlC2 bulk material and high-temperature infiltration of copper, i.e., hot-pressing and sintering micro-nano flaky Ti3AlC2 powder. Finally, high-temperature infiltration is used to make the ternary nano-layered Ti3AlC2 react and diffuse with copper in situ at high temperature. Among them, Al atoms are decomposed from Ti3AlC2 and dissolved in the copper matrix. The highly oriented and densified Ti3AlC2 is transformed into a highly oriented non-stoichiometric TiCx as a ceramic phase, which is evenly distributed in the copper matrix. Its microstructure is a shell-like "brick-mud" structure. In the composite Cracks in the composite material are prone to deflection, absorbing energy and improving the toughness of the material. In addition, since the precursor Ti3AlC2 is a dense block material, the volume fraction of its ceramic phase is higher than that of the ceramic phase of the copper-based composite material prepared in the existing related technology, which is beneficial to the simultaneous improvement of the strength, hardness, modulus and wear resistance of the composite material. Due to the shell-like bionic structure design, the structural characteristics of the composite material are highly oriented and the two phases are evenly distributed. The matrix copper has good orientation connectivity. Compared with other ceramic-reinforced copper-based composite materials, under the same conductivity, the shell-like bionic structure copper-based composite material prepared by this patent has higher strength, hardness and other mechanical properties.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] TiC of the shell-like bionic structure of the present invention x A reinforced copper-based composite material and a preparation method thereof, comprising the following steps:

[0009] Step 1: Preparation of highly oriented Ti3AlC2 dense blocks:

[0010] The micro-nano flaky Ti3AlC2 powder was loaded into a hot pressing sintering mold, vacuum hot pressing sintered under a protective atmosphere, and then cooled to room temperature in the furnace to obtain a Ti3AlC2 bulk material with a shell-like biomimetic structure.

[0011] Step 2, in-situ reaction diffusion treatment:

[0012] The copper blocks are placed on the upper and lower sides of the Ti3AlC2 block material with shell-like biomimetic structure in step 1 and loaded into a graphite crucible together. Under a protective atmosphere, vacuum heating is carried out to react and diffuse with copper in situ. After cooling with the furnace, a TiC2 flake with shell-like biomimetic structure is obtained. x reinforced copper-based composites;

[0013] The average particle size of the micro-nano flaky Ti3AlC2 powder in step 1 is 1-10 μm, and the average thickness is 0.1-1 μm;

[0014] The vacuum hot pressing sintering in step 1 is specifically as follows: heating from room temperature to 1000°C at a heating rate of 5-10°C / min, then heating to 1100-1200°C at a heating rate of 5°C / min, loading the pressure to 30MPa, and holding the temperature for at least 2h; the protective atmosphere is argon; the vacuum degree is 10 -3 Pa;

[0015] The mass ratio of the copper block to the Ti3AlC2 bulk material in step 2 is not less than 5:1;

[0016] The copper block in step 2 is electrolytic copper; the protective atmosphere is argon; the vacuum heating is specifically, the vacuum degree is 10 -3 Pa, at a heating rate of 5°C / min, from room temperature to 1000°C, then at a heating rate of 2°C / min to 1150°C-1300°C, with a holding time of 10-180 min;

[0017] The shell-like biomimetic structure of the present invention is a sheet of TiC x The reinforced copper-based composite material is prepared by the above method. The copper-based composite material with shell-like bionic structure includes ceramic-ceramic phase TiC x and matrix copper; ceramic phase TiC x It is highly oriented and evenly distributed in the matrix copper, among which TiC x The volume fraction of tantalum is 45-65%, and the balance is copper.

[0018] The shell-like bionic structure of the flaky TiC x The hardness of the reinforced copper-based composite material is 2.8-4.8GPa.

[0019] The shell-like bionic structure of the flaky TiC x The flexural strength of the reinforced copper-based composite material is 1.2-1.4GPa.

[0020] The shell-like bionic structure of the flaky TiC x The conductivity of the enhanced copper-based composite material is 3-5MS / m.

[0021] Compared with the prior art, the present invention has a shell-like biomimetic structure of TiC flakes. x Reinforced copper-based composite materials have the following beneficial effects:

[0022] The present invention provides a sheet-like TiC with a shell-like bionic structure xTo strengthen copper-based composite materials, hot pressing and sintering are used to prepare Ti3AlC2 blocks with shell-like biomimetic structures. That is, micro-nano flaky Ti3AlC2 powders are hot-pressed and sintered to prepare highly oriented and densified Ti3AlC2 block materials as precursor materials for the "brick-mud structure". Then, in-situ reaction diffusion treatment is carried out with copper at high temperature. Among them, Al atoms are decomposed from Ti3AlC2 and dissolved in the copper matrix. The highly oriented and densified Ti3AlC2 is transformed into highly oriented non-stoichiometric TiCx as a ceramic phase, which is uniformly distributed in the copper matrix. Its microstructure exhibits a shell-like "brick-mud" structure. Cracks in the composite material are easily deflected, absorbing energy and improving the toughness of the material. Compared to infiltrating copper into a porous ceramic skeleton at high temperature, the in-situ diffusion of copper into a dense precursor Ti3AlC2 bulk material is more difficult to prepare due to the relatively small contact surface area. Furthermore, ensuring a high degree of orientation of the ceramic phase is difficult to achieve. The volume fraction of the ceramic phase can be effectively controlled within the range of 45-65 vol%, thereby effectively regulating and improving the electrical conductivity, thermal conductivity, strength, hardness, modulus, and wear resistance of the composite material. Because the ceramic phase in the composite material is highly oriented, the copper matrix exhibits good orientation connectivity, which is beneficial for improving the electrical and thermal conductivity of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a photo of the Ti3AlC2 bulk material with a shell-like bionic structure prepared by the present invention;

[0024] Figure 2 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 15 minutes in Example 1 of the present invention. x Microstructure diagram of composite materials;

[0025] Figure 3 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 15 minutes in Example 1 of the present invention. x XRD results of composite materials;

[0026] Figure 4 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 15 minutes in Example 1 of the present invention. x Three-point bending stress-strain curve of composite materials;

[0027] Figure 5 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 30 minutes in Example 2 of the present invention. x Microstructure diagram of composite materials;

[0028] Figure 6This is the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 30 minutes in Example 2 of the present invention. x XRD results of composite materials;

[0029] Figure 7 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 30 minutes in Example 2 of the present invention. x Three-point bending stress-strain curve of composite materials;

[0030] Figure 8 This is Example 3 of the present invention, the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 90 minutes x Microstructure diagram of composite materials;

[0031] Figure 9 This is Example 3 of the present invention, the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 90 minutes x Three-point bending stress-strain curve of composite materials;

[0032] Figure 10 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 180 minutes in Example 4 of the present invention. x Microstructure diagram of composite materials;

[0033] Figure 11 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 180 minutes in Example 4 of the present invention. x Three-point bending stress-strain curve of composite materials;

[0034] Figure 12 The shell-like biomimetic structure Cu-TiC prepared in Examples 1-4 of the present invention x Volume fraction of the ceramic phase in the composite;

[0035] Figure 13 The shell-like biomimetic structure Cu-TiC prepared in Examples 1-4 of the present invention x Changes in Vickers hardness of composite materials;

[0036] Figure 14 The shell-like biomimetic structure Cu-TiC prepared in Examples 1-4 of the present invention x Changes in the electrical conductivity of the composite material. DETAILED DESCRIPTION

[0037] To further illustrate the technical means and effects employed by the present invention to achieve its intended objectives, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention is provided in conjunction with the accompanying drawings and preferred embodiments. In the following description, different references to "one embodiment" or "embodiment" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics of one or more embodiments may be combined in any suitable manner.

[0038] The specific scheme of the present invention is as follows:

[0039] The embodiment of the present invention provides a sheet of TiC with a shell-like biomimetic structure x Reinforced copper-based composite materials. The shell-like biomimetic copper-based composite material is obtained by hot-pressing and sintering micro-nano flaky Ti3AlC2 powder into a densified, shell-like biomimetic Ti3AlC2 bulk material. The microstructure exhibits a highly oriented structure. The hot-pressing sintering temperature is 1200°C, the pressure is 30MPa, and the holding time is at least 2 hours. The Ti3AlC2 bulk material and metallic copper are subjected to in-situ diffusion treatment at a temperature of 1150-1300°C for at least 10 minutes, preferably 15, 30, 90, or 180 minutes. The above process is completed in a vacuum environment and under protective gas.

[0040] The present invention is further described below by means of specific experimental examples:

[0041] In the following examples, Ti3AlC2 bulk materials with shell-like biomimetic structures and Cu-TiC with shell-like biomimetic structures were prepared using the same hot pressing furnace and high temperature furnace. x Composite materials.

[0042] Example 1

[0043] This embodiment uses a TiC flake with a shell-like bionic structure. x The reinforced copper-based composite material comprises the following preparation steps:

[0044] Step 1: Prepare Ti3AlC2 blocks with shell-like biomimetic structures:

[0045] 100g of micro-nano flaky Ti3AlC2 powder with an average particle size of 1.5μm and an average thickness of 0.4μm was weighed and loaded into a hot pressing sintering mold. The temperature was first increased from room temperature to 1000℃ at a heating rate of 10℃ / min, and then increased to 1200℃ at a heating rate of 5℃ / min. The pressure was applied to 30MPa and the temperature was kept at this temperature for 2h. The material was then cooled to room temperature and taken out to obtain a Ti3AlC2 bulk material with a shell-like bionic structure.

[0046] Step 2, in-situ reaction diffusion treatment:

[0047] The Ti3AlC2 bulk material with shell-like biomimetic structure and copper block were placed in a graphite crucible and placed in a high-temperature furnace. The mass ratio of the copper block to the Ti3AlC2 bulk material was not less than 5:1. Under protective gas and vacuum conditions, the temperature was first increased from room temperature to 1000°C at a rate of 5°C / min, and then increased to 1250°C at a rate of 2°C / min and kept at this temperature for 15 minutes for in-situ reaction diffusion treatment. After cooling in the furnace, TiC flakes with shell-like biomimetic structure were obtained. x Reinforced copper-based composites;

[0048] Figure 1 This is a photo of the Ti3AlC2 bulk material with shell-like biomimetic structure prepared by the present invention. Figure 2 and Figure 3 They are respectively Example 1 of the present invention, the shell-like biomimetic structure Cu-TiC prepared by in-situ diffusion and heat preservation for 15 minutes x The microstructure diagram and XRD results of the composite material show that the copper-based composite material with shell-like biomimetic structure can be obtained by adopting the preparation method of this patent, in which the ceramic phase TiC x It is highly oriented and evenly distributed in the copper matrix. It can also be seen that there are darker areas in the matrix. Combined with the diffraction direction of XRD (vertical and parallel), TiC x It shows anisotropy on (111), (200), (311) and (222) crystal planes, proving that TiC x It has a highly oriented structure. In addition, there is a small amount of AlCu2Ti, which proves that the darker area is the in-situ reaction diffusion area. This is because the short holding time leads to incomplete diffusion and the formation of intermetallic compounds. Figure 4 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ diffusion and heat preservation for 15 minutes in Example 1 of the present invention. x The three-point bending stress-strain curve of the composite material shows a bending strength of 1437 MPa. Figure 12 、 13 and 14. The copper-based composite material prepared in Example 1 has a ceramic phase volume fraction of 63 vol%, a Vickers hardness of 4.75 GPa, and electrical conductivities parallel to and perpendicular to the shell-like structure of the copper-based composite material are 2.16 MS / m and 3.03 MS / m, respectively.

[0049] Example 2

[0050] This embodiment uses a TiC flake with a shell-like bionic structure. x The preparation steps of the reinforced copper-based composite material are as follows:

[0051] Step 1 is consistent with Example 1;

[0052] Step 2: The in-situ reaction diffusion treatment time is 30 minutes, and the rest of the contents remain unchanged.

[0053] Figure 5 and Figure 6 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ diffusion and heat preservation for 30 minutes in Example 2 of the present invention. x The microstructure diagram and XRD results of the composite material show that after in-situ diffusion and heat preservation for 30 minutes, its microstructure is a shell-like bionic structure. Compared with the Cu-TiC prepared in Example 1 and Example 2, x There is no obvious dark area in the matrix of the composite material. Combined with the XRD results, it can be seen that TiC x The results show anisotropy, with a highly oriented and uniform distribution in the copper matrix. Furthermore, the absence of other reaction products indicates that the in-situ reaction diffusion is relatively complete. Figure 7 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ diffusion and heat preservation for 30 minutes in Example 1 of the present invention. x The three-point bending stress-strain curve of the composite material shows a bending strength of 1349 MPa. Figure 12 、 13 and 14. The copper-based composite material prepared in Example 2 has a ceramic phase volume fraction of 60 vol%, a Vickers hardness of 3.65 GPa, and electrical conductivities parallel to and perpendicular to the shell-like structure of the copper-based composite material are 2.46 MS / m and 3.57 MS / m, respectively.

[0054] Example 3

[0055] This embodiment uses a TiC flake with a shell-like bionic structure. x The preparation steps of the reinforced copper-based composite material are as follows:

[0056] Step 1 is consistent with Example 1;

[0057] Step 2: The in-situ reaction diffusion treatment time is 90 min, and the rest of the contents remain unchanged.

[0058] Figure 8 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ diffusion and heat preservation for 90 minutes in Example 3 of the present invention. x The microstructure of the composite material shows that the ceramic phase TiC x The oriented structure is still retained, but the organizational structure changes with the extension of the holding time. x In both the longitudinal and transverse directions, it shows TiC x Crystal growth trend. Figure 9 This is Example 3 of the present invention, the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 90 minutes xThe three-point bending stress-strain curve of the composite material shows a bending strength of 1217 MPa. Figure 12 、 13 and 14. The copper-based composite material prepared in Example 3 has a ceramic phase volume fraction of 52.5 vol%, a Vickers hardness of 2.98 GPa, and electrical conductivities of the copper-based composite material parallel to and perpendicular to the shell-like bionic structure are 2.86 MS / m and 2.92 MS / m, respectively.

[0059] Example 4

[0060] This embodiment uses a TiC flake with a shell-like bionic structure. x The preparation steps of the reinforced copper-based composite material are as follows:

[0061] Step 1 is consistent with Example 1; in step 2, the in-situ reaction diffusion treatment time is 180 min, and the rest of the contents remain unchanged.

[0062] Figure 10 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 180 minutes in Example 4 of the present invention. x The microstructure of the composite material shows that the ceramic phase TiC x The orientation structure is retained, and its orientation degree is lower than that of Examples 1, 2 and 3. This is because the ceramic phase TiC x In both longitudinal and transverse directions, TiC x The crystals grew significantly. Figure 11 This is the shell-like biomimetic structure Cu-TiC prepared by in-situ reaction diffusion and heat preservation for 180 minutes in Example 3 of the present invention. x The three-point bending stress-strain curve of the composite material shows a bending strength of 1158 MPa. Figure 12 、 13 and 14. The copper-based composite material prepared in Example 4 has a ceramic phase volume fraction of 48.5 vol%, a Vickers hardness of 2.81 GPa, and electrical conductivities of the copper-based composite material parallel to and perpendicular to the shell-like bionic structure are 2.4 MS / m and 2.57 MS / m, respectively.

[0063] Example 5

[0064] The same as Example 1, except that the micro-nano flaky Ti3AlC2 powder was hot-pressed and sintered at 1100°C, the pressure was 30 MPa, and the holding time was 2 h. The prepared Ti3AlC2 bulk material had a slightly lower degree of densification than the bulk Ti3AlC2 material prepared in Example 1, and there were pore defects in the material and the Ti3AlC2 orientation was poor, resulting in the lack of shell-like structural characteristics at the microscopic level, making it difficult to prepare a copper-based composite material with a shell-like biomimetic structure.

[0065] Comparative Example 1

[0066] The same as Example 1, except that the hot pressing sintering pressure used in step 1 is 10 MPa, the micro-nano flaky Ti3AlC2 powder has poor preferential orientation, and the corresponding material densification degree is lower than that of Example 1, which not only affects the preparation of copper-based composite materials with shell-like bionic structures but also reduces the material strength, hardness and wear resistance.

[0067] Comparative Example 2

[0068] Same as Example 1, except that step 2 uses an in-situ reaction diffusion temperature of 1400°C, Ti3AlC2 reacts and diffuses with copper faster, and the in-situ generated TiC x The crystal growth size and the degree of complete reaction of Ti3AlC2 are uncontrollable, which makes the microstructure of the material difficult to control, and thus it is difficult to synergistically improve the mechanical properties, electrical properties and thermal properties of the material.

[0069] Comparative Example 3

[0070] The same as Example 1, except that the in-situ reaction diffusion time in step 2 is 5 minutes, the micro-nano flaky Ti3AlC2 powder reacts incompletely with copper, and the presence of partial Ti3AlC2 in local areas of the material not only affects the electrical and thermal conductivity but also easily causes stress concentration, resulting in poor deformation ability of the material and prone to brittle fracture.

[0071] Comparative Example 4

[0072] Same as Example 1, except that the in-situ reaction diffusion time in step 2 is 240 min, and the TiC generated by the in-situ reaction is x The crystals will become coarse and the structural orientation will deteriorate. The final copper-based composite material will not exhibit a shell-like structure at the microscopic level. The corresponding material hardening efficiency is low and the strengthening and toughening are difficult to improve synergistically, affecting the service performance of the material, such as wear resistance and resistance to arc erosion.

[0073] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Any simple modifications, equivalent changes, and modifications made to the above embodiment based on the technical essence of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. TiC with shell-like bionic structure x A reinforced copper-based composite material, characterized in that: The TiC x Reinforced copper matrix composites including ceramic phase TiC x and the matrix copper, the ceramic phase TiC x It is highly oriented and evenly distributed in the matrix copper; The ceramic phase TiC x The volume fraction is 45-65%, and the balance is copper; The TiC of the shell-like bionic structure x The hardness of the reinforced copper-based composite material is 2.8-4.8 GPa, the bending strength is 1.2-1.4 GPa, and the conductivity is 3-5 MS / m.

2. A TiC based on the shell-like bionic structure of claim 1 x A method for preparing a reinforced copper-based composite material, characterized in that: The following steps are involved: Step (1): loading the micro-nano flaky Ti3AlC2 powder into a hot pressing sintering mold, performing vacuum hot pressing sintering under a protective atmosphere, and then cooling the mixture to room temperature with the furnace to obtain a Ti3AlC2 bulk material having a shell-like bionic structure; Step (2): placing the copper block on the upper and lower sides of the Ti3AlC2 block material with the shell-like bionic structure in step 1 and loading them into a graphite crucible together, vacuum heating under a protective atmosphere, in-situ reaction diffusion with the copper, and cooling with the furnace to obtain a TiC flake with a shell-like bionic structure. x Reinforced copper matrix composites; The vacuum hot pressing sintering in step (1) is specifically to increase the temperature from room temperature to 1000°C at a heating rate of 5-10°C / min, and then to 1100-1200°C at a heating rate of 5°C / min, and to apply pressure to 30MPa, and to keep the temperature and pressure for at least 2h; In step (2), the vacuum heating is specifically: heating from room temperature to 1000°C at a heating rate of 5°C / min, and then heating to 1150°C-1300°C at a heating rate of 2°C / min, and the holding time is 10-180min.

3. TiC of shell-like bionic structure according to claim 2 x A method for preparing a reinforced copper-based composite material, characterized in that: The average particle size of the micro-nano flaky Ti3AlC2 powder in step (1) is 1-10 μm, and the average thickness is 0.1-1 μm.

4. The TiC of shell-like bionic structure according to claim 2 x A method for preparing a reinforced copper-based composite material, characterized in that: In steps (1) and (2), the protective atmosphere is argon; the vacuum degree of the vacuum is 10 -3 Pa.

5. The TiC of shell-like biomimetic structure according to claim 2 x A method for preparing a reinforced copper-based composite material, characterized in that: The mass ratio of the copper block to the Ti3AlC2 bulk material in step (2) is not less than 5:

1.

6. The TiC of shell-like bionic structure according to claim 2 x A method for preparing a reinforced copper-based composite material, characterized in that: The copper block in step (2) is electrolytic copper.

Citation Information

Patent Citations

  • Preparation method and application of titanium modified Ti3AlC2 reinforced copper-based electrical contact

    CN109524251A

  • Cu and Ti3AlC2 functionally graded material for pantograph pan and preparation method of Cu and Ti3AlC2 functionally graded material

    CN112935250A

  • Ni-doped Ti3AlC2 / Cu composite material for inhibiting decomposition of Ti3AlC2 and preparation method of Ni-doped Ti3AlC2 / Cu composite material

    CN113512658A

  • Cu-TiCx composite material and preparation method thereof

    CN114427049A

  • High-volume-fraction ceramic-metal layered composite material and preparation method thereof

    CN107326211A